Effects of Carnosine, Ankaferd, and Silver Sulfadiazine on an Experimental Burn Model: Roles of Irisin and HSP70 - Kocaman, Nevin; Altun, Serdar; Bal, Ali; Ozcan, Erhan Cahit; Sarac, Mehmet; Artas, Gokhan; Kuloglu, Tuncay (Oxford Univ Press, 2021)
In this study, the effects of carnosine, ankaferd, and 1% silver sulfadiazine applied topically on second-degree burns were investigated and the roles of irisin and Heat shock protein 70 (HSP70) in this healing process were evaluated. Ninety male albino rats were used and divided into five groups. The groups were classified as control, burn, burn + carnosine (CAR), burn + ankaferd (ABS), and burn + silver sulfadiazine (SS). It was found that level of irisin increased in the first week and decreased in the second week in the burn and CAR groups. In the ABS and SS groups, the level of irisin was determined that started to increase in the first week and continued to increase in the second week. The level of HSP70 was found to increased in the first week in burn and CAR groups and decreased in the second week, but started to increase in the second week in ABS and SS groups. Both levels of irisin and HSP70 were observed to decreased in all treatment groups in the third week. In this study, it was shown that ankaferd and silver sulfadiazine treatments cause an increase in the irisin levels in the early period and a gradually increase in HSP70 levels in the later period in burns. The inflammatory response was observed to be limited in the early period in the ankaferd and sulfadiazin groups. It was concluded that these findings were effective in early wound healing in burns.
Keywords: Protects; Injury; Rats